IPTEK BAGI MASYARAKAT : âLetâs Be Survivor Cardioâ UPAYA REGULASI PERILAKU BERESIKO CARDIOVASCULAR DISEASE TAHUN 2014 - Nurwidyaningtyas, Wiwit; Kholifah, Siti (Jurnal Kesehatan Mesencephalon, 2017)
Abstract : Various risk factors such as smoking, hypertension, chronic elevated blood sugar levels, increased blood fat levels that not controlled and the lack of sporting activity are directly proportional to the increase in the prevalence of cardiovascular disease (CVD). But people generally do not realize that these risk factors closely related to unhealthy lifestyles inherent in public behavior, including the family environment. Lack of family awareness aboutÂ risk of CVD patterns become an important point in the risk factor control strategies through the dissemination and application of a pilot project in a targeted area. This program aims to encourage families built to be able to control or reduce behaviors or habits that lead to CVD risk behavior. In Higher Education program funded IbM we try to apply the smart card on the family built that called logbook for monitoring indicators of risk behavior includes, waist circumference, blood pressure, blood glucose monitoring and blood fat, diet and exercise and smoking habits. This program is facilitated by local cadres who previously had trainedÂ on CVD risk factors during cadre training program in Rampal Celaket Public Health Services working area has been done in 2013. Then family discipline built for the implementation of an advanced program